2009
DOI: 10.1002/chp.20044
|View full text |Cite
|
Sign up to set email alerts
|

The use of medical information in Nigeria: The influence of gender and status

Abstract: The male resident doctors were more concerned with passing their professional examinations, and that was their main reason for searching medical information. The other groups searched information mostly to update their knowledge. Better medical practice was not an important reason to any of the groups. This attitude should be changed through continuing medical education (CME), which refers to a specific form of continuing education that helps those in the medical field maintain competence and learn about new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A number of studies [9, 16, 17, 21, 22] have addressed patterns of internet use among medical practitioners. Also, researchers have studied the demographic factors that influence use of internet resources among different categories of professionals including medical doctors [16, 18, 21, 26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies [9, 16, 17, 21, 22] have addressed patterns of internet use among medical practitioners. Also, researchers have studied the demographic factors that influence use of internet resources among different categories of professionals including medical doctors [16, 18, 21, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Also, researchers have studied the demographic factors that influence use of internet resources among different categories of professionals including medical doctors [16, 18, 21, 26]. However, there is a dearth of information on the influence of internet accessibility and demographic factors on utilization of web-based health information resources among resident doctors in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The adopted view in the studies that are described here is often, intentionally or unintentionally, either individual or source oriented, with little or no focus on the context of the work practices. For example, prior research has found that printed materials such as medical textbooks and journals are popular sources of information (e.g., Nobert & Lwoga, ; Okoro & Okoro, ). Most studies in developing countries also indicate that interpersonal processes, such as contacts with patients as well as colleagues and other health‐care providers, remain the major source of medical information for health professionals (e.g., Kapiriri & Bondy, ; Tumwikirize et al., ; Martinez‐Silveira & Oddone, ; Ocheibi & Buba, ; Callen, Buyankhishig, & McIntosh, ; Nobert & Lwoga, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] For example, Europeans are challenged to assure that physicians may circulate freely to practice among countries of the European Union and to reconcile differences between nations that require participation in continuing education and those that do not. 6 A recent study 5 suggests doctors in Nigeria require education not only to effectively search medical information but also in learning how to apply the information to practice. In Southeast Asia, as Vietnam 2 adjusts to membership in the World Trade Organization and to a fast growing market economy, the nation also faces difficulties in identifying and allocating resources to close performance gaps between skilled clinicians of the public sector and the more recently employed practitioners of the private sector.…”
mentioning
confidence: 99%
“…All forms of stakeholders in health care share interest in systems that assess and serve the learning needs of clinicians and qualify those clinicians as lifelong learners with privileges and credentials to practice. [1][2][3][4][5][6][7][8] For example, Europeans are challenged to assure that physicians may circulate freely to practice among countries of the European Union and to reconcile differences between nations that require participation in continuing education and those that do not. 6 A recent study 5 suggests doctors in Nigeria require education not only to effectively search medical information but also in learning how to apply the information to practice.…”
mentioning
confidence: 99%